2004
DOI: 10.1023/b:emas.0000003565.25474.8f
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Sodium and Potassium in the Water from Wetlands in Minnesota that Contained Malformed Frogs Affect the Rate ofXenopusDevelopment

Abstract: Water samples were collected between 1999 and 2000 from wetlands in Minnesota that contained malformed frogs. The water samples were analyzed for 14 minerals/ions and screened for the presence of biologically active compounds using Xenopus laevis. Results indicated that water from two sites, CWB and ROI2, induced severe retardation with embryo lengths reduced 20% after 96 hr of development. The developmental delay observed with water from ROI2 was alleviated by supplementation with sodium, while both sodium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Exposure to metals such as zinc, copper, lead, and cadmium has previously been shown to reduce tadpole survival before metamorphosis [84], as well as other negative effects on the development of embryos and larvae of Xenopus laevis in South Africa [93]; in comparison with the present investigation, the concentrations of these metals are lower in the tested dilutions than for those other studies. Other investigations [94,95] report that metals such as sodium, calcium, potassium, and manganese can generate lethal effects and morphological alterations in the development of amphibian embryos, findings similar to the results obtained in this research.…”
Section: Xenopus Laevissupporting
confidence: 90%
“…Exposure to metals such as zinc, copper, lead, and cadmium has previously been shown to reduce tadpole survival before metamorphosis [84], as well as other negative effects on the development of embryos and larvae of Xenopus laevis in South Africa [93]; in comparison with the present investigation, the concentrations of these metals are lower in the tested dilutions than for those other studies. Other investigations [94,95] report that metals such as sodium, calcium, potassium, and manganese can generate lethal effects and morphological alterations in the development of amphibian embryos, findings similar to the results obtained in this research.…”
Section: Xenopus Laevissupporting
confidence: 90%
“…Although subsequent laboratory studies implicated a developmental contaminant (Burkhart et al, 1998;Fort et al, 1999aFort et al, ,b, 2001Bridges et al, 2004) and identified numerous agricultural pollutants within water from sites where frog deformities occurred (Fort et al, 1999b), no single causative agent could be identified. To further complicate the issue, there was also some suggestion that mineral deficiencies in the water at sites where malformations occurred may be a contributing factor (Fort et al, 1999b;Tietge et al, 2000;Garber, 2002;Garber et al, 2004).…”
Section: Deformitiesmentioning
confidence: 99%
“…A ampla ocorrência de anfíbios com deformidades e a importância da água doce na cadeia alimentar vêm gerando um aumento da preocupação da sociedade com a saúde pública. Várias hipóteses têm sido propostas para explicar essas deformidades, incluindo o aumento da exposição aos raios ultravioletas-B devido à diminuição da camada de ozônio, predação, fragmentação de hábitats, escassez de alimento, aumento da exposição a parasitas, poluentes e retinóides (Blaustein et al 1997, Sessions et al 1999, Pounds 2001, Garber et al 2004.…”
Section: Vertebradosunclassified